2021
DOI: 10.1016/j.intimp.2021.107968
|View full text |Cite
|
Sign up to set email alerts
|

“Impact of pentaglobin in severe COVID 19 pneumonia- a prospective study.”

Abstract: Background The current COVID-19 pandemic has become a global public health crisis and presents a serious challenge in treatment of severe COVID pneumonia patients. With an imperative need for an effective treatment, we aimed to study the effectiveness of Pentaglobin, an intravenous immunoglobin in the treatment of severe Covid-19 pneumonia patients. Methods This is an open-label non-randomised controlled study. Patients in the study group (n=17) received Pentaglobin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, there were some case reports and small studies regarding the usage of Pentaglobin as adjunctive therapy in COVID-19 (185)(186)(187)(188). Although in a large retrospective cohort study, no significant difference in mortality was observed (n=316, p=0.374), a subgroup of severe COVID-19 patients who have not yet received invasive mechanical ventilation may benefit from Pentaglobin therapy (p=0.063).…”
Section: Pentaglobinmentioning
confidence: 99%
“…Furthermore, there were some case reports and small studies regarding the usage of Pentaglobin as adjunctive therapy in COVID-19 (185)(186)(187)(188). Although in a large retrospective cohort study, no significant difference in mortality was observed (n=316, p=0.374), a subgroup of severe COVID-19 patients who have not yet received invasive mechanical ventilation may benefit from Pentaglobin therapy (p=0.063).…”
Section: Pentaglobinmentioning
confidence: 99%